The Influence of Digital Banking Services on Rentability and Risk Profile of Banks with the Covid-19 Pandemic and Capital as a Moderating Variable - Fauzi Sain; Atma Hayat (Jurnal Office, 2023)
Digital banking services are electronic banking services that are developed through the use of customer data in order to provide services to customers quickly, easily, and in accordance with the wishes of customers, and can be carried out by customers themselves, taking into account aspects of security and confidentiality of customer data. This study aims to analyze the effect of digital banking services on profitability and risk profile and analyze the Covid-19 pandemic and capital moderating the effect of digital banking services on profitability and risk profile. This research is a type of causality research that uses secondary data from published reports of 59 conventional commercial banks with Indonesian legal entities over a 7-year period from 2015 to 2021. The sampling technique uses purposive sampling and data analysis in this study uses the Partial Least Square model through the product indicator approach analysis technique. Based on the results of the analysis, digital banking services have a positive and significant effect on profitability and risk profile, the Covid-19 pandemic has not moderated digital banking services on profitability and risk profile, and capital has moderated digital banking services on profitability and risk profile